2021
DOI: 10.1515/revneuro-2020-0108
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated central nervous system manifestations, mental and neurological symptoms: a systematic review and meta-analysis

Abstract: The ongoing pandemic of Coronavirus disease 2019 (COVID-19) has infected more than 27 million confirmed cases and 8,90,000 deaths all around the world. Verity of viral infections can infect the nervous system; these viral infections can present a wide range of manifestation. The aim of the current study was to systematically review the COVID-19 associated central nervous system manifestations, mental and neurological symptoms. For that we conducted a comprehensive systematic literature review of four online da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 73 publications
0
36
1
2
Order By: Relevance
“…These results were in concordance to cross-sectional study done by Carcamo Garcia et al [ 7 ] who found that the most common neurological symptoms were headache (72%), hypogeusia or ageusia (41%), hyposmia or anosmia (40%). While they were in discordant to Study conducted by Soltani et al [ 8 ] which indicated that, the prevalence of CNS or mental associated disorders was 50.68%. The most prevalent symptoms were hyposmia/ anosmia/ olfactory dysfunction, while the prevalence of depression and anxiety was 3.52%.…”
Section: Discussioncontrasting
confidence: 41%
“…These results were in concordance to cross-sectional study done by Carcamo Garcia et al [ 7 ] who found that the most common neurological symptoms were headache (72%), hypogeusia or ageusia (41%), hyposmia or anosmia (40%). While they were in discordant to Study conducted by Soltani et al [ 8 ] which indicated that, the prevalence of CNS or mental associated disorders was 50.68%. The most prevalent symptoms were hyposmia/ anosmia/ olfactory dysfunction, while the prevalence of depression and anxiety was 3.52%.…”
Section: Discussioncontrasting
confidence: 41%
“…In particular, home confinement and quarantine have led to prolonged separation from relatives and loved ones [ 5 , 6 ], contributing to increasing the levels of distress not only for people with pre-existing mental disorders, but also for those affected by COVID-19, healthcare professionals, and the general population as a whole [ 7 , 8 , 9 , 10 , 11 ]. Furthermore, the SARS-CoV-2 also presents neurotropism and may thus directly trigger possible neuropsychiatric manifestations [ 12 , 13 , 14 ]. The effects of the COVID-19 pandemic on mental health include the rise of anxiety and depressive symptoms, somatic complaints [ 6 , 15 , 16 ], disruption of circadian rhythms, with frequent sleep disorders [ 17 ], phobias, cognitive deficits, and traumatic experiences.…”
Section: Introductionmentioning
confidence: 99%
“…We performed the analysis using Stata software 14.0. COVID-19 cases, viral coinfection prevalence, and types of viruses were extracted [14][15][16][17][18].…”
mentioning
confidence: 99%